Structure of Galectin-3 bound to a model membrane containing ganglioside GM1 - Vander Zanden, Crystal M.; Majewski, Jaroslaw; Weissbarth, Yvonne; Browne, Danielle F.; Watkins, Erik B.; Gabius, Hans-Joachim (Biophysical journal, 2023)
Galectin-3 (Gal-3) is a β-galactosidase-binding protein involved in various biological processes, including neuronal growth and adhesion. The pairing of Gal-3 with ganglioside GM1’s pentasaccharide chain at the outer leaflet of the plasma membrane, which triggers downstream cell-signaling cascades, seems to be involved in these processes. A crucial feature of Gal-3 is its ability to form oligomers and supramolecular assemblies that connect various carbohydrate-decorated molecules. Although we know the atomistic structure of Gal-3 bound to small carbohydrate ligands, it remains unclear how Gal-3 binds GM1 in a membrane. Furthermore, the influence of this interaction on Gal-3’s structure and oligomeric assembly has to be elucidated. In this study, we used X-ray reflectivity (XR) from a model membrane to determine the structure and surface coverage of Gal-3 bound to a membrane containing GM1. We observed that the carbohydrate recognition domain interacts with GM1’s pentasaccharide, while the N-terminal domain is pointed away from the membrane, likely to facilitate protein-protein interactions. In a membrane containing 20 mol % GM1, Gal-3 covered ∼50% of the membrane surface with one Gal-3 molecule bound per 2130 Å2. We used molecular dynamics simulations and Voronoi tessellation algorithms to build an atomistic model of membrane-bound Gal-3, which is supported by the XR results. Overall, this work provides structural information describing how Gal-3 can bind GM1’s pentasaccharide chain, a prerequisite for triggering regulatory processes in neuronal growth and adhesion.